Characterization of the Prophage Repertoire of African Salmonella Typhimurium ST313 Reveals High Levels of Spontaneous Induction of Novel Phage BTP1 - Owen, Siân V.; Wenner, Nicolas; Canals, Rocío; Makumi, Angela; Hammarlöf, Disa L.; Gordon, Melita A.; Aertsen, Abram; Feasey, Nicholas A.; Hinton, Jay C. D. (Frontiers in Microbiology, 2017)
In the past 30 years, Salmonella bloodstream infections have become a significant health problem in sub-Saharan Africa and are responsible for the deaths of an estimated 390,000 people each year. The disease is predominantly caused by a recently described sequence type of Salmonella Typhimurium: ST313, which has a distinctive set of prophage sequences. We have thoroughly characterized the ST313-associated prophages both genetically and experimentally. ST313 representative strain D23580 contains five full-length prophages: BTP1, Gifsy-2D23580, ST64BD23580, Gifsy-1D23580, and BTP5. We show that common S. Typhimurium prophages Gifsy-2, Gifsy-1, and ST64B are inactivated in ST313 by mutations. Prophage BTP1 was found to be a functional novel phage, and the first isolate of the proposed new species “Salmonella virus BTP1”, belonging to the P22virus genus. Surprisingly, ∼109 BTP1 virus particles per ml were detected in the supernatant of non-induced, stationary-phase cultures of strain D23580, representing the highest spontaneously induced phage titer so far reported for a bacterial prophage. High spontaneous induction is shown to be an intrinsic property of prophage BTP1, and indicates the phage-mediated lysis of around 0.2% of the lysogenic population. The fact that BTP1 is highly conserved in ST313 poses interesting questions about the potential fitness costs and benefits of novel prophages in epidemic S. Typhimurium ST313.